2014
DOI: 10.5296/jpag.v4i2.5844
|View full text |Cite
|
Sign up to set email alerts
|

The promotional tools and situational factors’ impact on consumer buying behaviour and sales promotion

Abstract: We can see that companies spend a large portion of their budgets for sale promotion. The goal is to offer the merchandise more attractive and valuable. These ideas allow us to conclude that the institutions seek to manipulate the buying activities of consumers, and so begin a strong promotional campaigns or changes in pricing policies, with other measures. The purpose of this research is to study closely the taste of the customers in the various ISSN 2161-7104 2014 www.macrothink.org/jpag 180 promotional tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…No surprisingly these factors are in concordance with some studies carried on by (Arango, Huynh, & Sabetti, 2015;Azeem & Sharma, 2015;Schultz & Block, 2014). According to Kim and Park (1997) in Ashraf, Rizwan, Iqbal, and Khan (2014), the physical surroundings of the store inluence consumers purchase decision. In fact, when the interior of the shopping mall is designed all right, the probability of purchasing from there is high.…”
Section: Store Atmospheresupporting
confidence: 87%
See 1 more Smart Citation
“…No surprisingly these factors are in concordance with some studies carried on by (Arango, Huynh, & Sabetti, 2015;Azeem & Sharma, 2015;Schultz & Block, 2014). According to Kim and Park (1997) in Ashraf, Rizwan, Iqbal, and Khan (2014), the physical surroundings of the store inluence consumers purchase decision. In fact, when the interior of the shopping mall is designed all right, the probability of purchasing from there is high.…”
Section: Store Atmospheresupporting
confidence: 87%
“…Both academics and professionals have a long argued that the end-user's view of brand value is affected by sales promotion (Arce- Urriza et al, 2017;Schultz & Block, 2014). In one's element, Bhasin (2018), because of consumers' willingness to buy a product arises from the promotion activities so the authors found timely to make a purchase over sales promotion period (Ashraf et al, 2014).…”
Section: Sales Promotionmentioning
confidence: 99%
“…According to Ghafran Ashraf [15], their study confirmed that consumers buying behavior and sales promotion can be motivated through various kinds of elements, including promotion techniques such as free samples, price discounts, social surroundings and physical surrounding.…”
Section: Resultsmentioning
confidence: 97%
“…The goal is to offer the merchandise more attractive and valuable. Buy and test consumer products direct specific goals that can be achieved through efforts to boost sales in the short term, the implementation of consumers in stores, and get to the point of retail sale displays, and encouraging stores to store products and sales support for the efforts of staff [15]. This information allows us to conclude that the institutions seek to manipulate the buying activities of consumers, and so begin a strong promotional campaigns or changes in pricing policies, with other measures.…”
Section: Sales Promotionmentioning
confidence: 99%
“…If a promotion only depends on discounts, the effect may be limited (Familmaleki et al, 2015). Promotions like free gifts, lucky draws and performances also please shopping malls' visitors and lead to a higher visit frequency in the shopping complexes (Ashraf et al, 2014). The following hypothesis is drawn based on the literature review.…”
Section: Services Related Factors (Personal Service Price Advertisimentioning
confidence: 99%